# I need help with this ^

31

Step-by-step explanation:

5z-25=180

5z=180-25

5z=155

z=31

Answer: Im pretty sure its 155

Step-by-step explanation:

## Related Questions

Find an exact value of sin(17pi/12)

●✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎❀✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎●

Hi my lil bunny!

❧⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯☙

=

=

❧⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯⎯☙

●✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎❀✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎✴︎●

If this helped you, could you maybe give brainliest..?

Also Have a great day/night!

❀*May*❀

I have an answer and explanation but I can't type so search up the question you asked and you should get an answer and explanation from s0cratic.

Find the missing coefficient. (5d − 7)(5d − 6) = 25d2 ++ 42 5 65 –5 –65

-65d

Step-by-step explanation:

(5d − 7)(5d − 6)

Multiply it using FOIL method to find the missing term

Multiply 5d inside the second parenthesis and then multiply -7 inside second parenthesis

Now write all the terms together

Combine like terms

HEre -65d is missing

i do believe it is -65d because the equation will look like this in the end
-65d=-65d.

Which model represents the equation 4w+3=3w+6

Step-by-step explanation:

4w+3=3w+6 (subtract 3 from both sides)

-3       -3

4w=3w+3 (subtract 3w on both sides)

-3w  -3w

1w=3 (divide by 1)

w=3

Evaluate the function.
f(x)=-2x^2-7x+6

Find f(−3)

f(-3) = 9

Step-by-step explanation:

Step 1: Define

f(x) = -2x² - 7x + 6

f(-3) = x = -3

Step 2: Substitute and evaluate

f(-3) = -2(-3)² - 7(-3) + 6

f(-3) = -2(9) + 21 + 6

f(-3) = -18 + 21 + 6

f(-3) = 3 + 6

f(-3) = 9

Substituting x = -3 into the function f(x) = -2x^2 - 7x + 6, we get f(-3) = -33. Therefore, the value of the function at x = -3 is -33.

To evaluate the function f(x)=−2x ^2 −7x+6 at  x=−3, substitute  −3 for x in the function: f(−3)=−2{(−3) }^2 −7(−3)+6

Now, calculate each part of the expression:

(−3) ^2   is 9  because the square of  −3 is  9.

−2 times 9 is  −18 because −2⋅9 =−18.

−7 times −3 is  21 because −7⋅−3=21.

Now, plug these values back into the expression:

f(−3)=−18−21+6

f(−3)=(−18−21)+6=−39+6=−33

So, f(−3)=−33.

The value of the function

f(x)=−2x^ 2 −7x+6 at  x=−3 is  −33.

For more questions on function

brainly.com/question/11624077

#SPJ3

Find the lcm of 2,3,7 and tell me how u got ur answerif its CORRECT with ur reasoning ill give brainlest

42

Step-by-step explanation:

What value of x would make KM ∥ JN?Triangle J L N is cut by line segment K M. Line segment K M goes from side J L to side L N. The length of J K is x minus 5, the length of K L is x, the length of L M is x + 4, and the length of M N is x minus 3.

Complete the statements to solve for x.

By the converse of the side-splitter theorem, if JK/KL = , then KM ∥ JN.

Substitute the expressions into the proportion: StartFraction x minus 5 Over x EndFraction = StartFraction x minus 3 Over x + 4 EndFraction.

Cross-multiply: (x – 5)() = x(x – 3).

Distribute: x(x) + x(4) – 5(x) – 5(4) = x(x) + x(–3).

Multiply and simplify: x2 – x – = x2 – 3x.

Solve for x: x = .

x = 10

Step-by-step explanation:

By the converse of the side-splitter theorem, if , then KM ∥ JN.

Substitute the expressions into the proportion:

Cross-multiply:

(x – 5)(x+4) = x(x – 3).

Distribute:

Multiply and simplify:

Solve for x: x = 10

Therefore, the value of x that would make KM parallel to JN is 10.

What value of x would make KM ∥ JN?

Triangle J L N is cut by line segment K M. Line segment K M goes from side J L to side L N. The length of J K is x minus 5, the length of K L is x, the length of L M is x + 4, and the length of M N is x minus 3.

Complete the statements to solve for x.

By the converse of the side-splitter theorem, if JK/KL =

✔ NM/ML

, then KM ∥ JN.

Substitute the expressions into the proportion: StartFraction x minus 5 Over x EndFraction = StartFraction x minus 3 Over x + 4 EndFraction.

Cross-multiply: (x – 5)(

✔ x + 4

) = x(x – 3).

Distribute: x(x) + x(4) – 5(x) – 5(4) = x(x) + x(–3).

Multiply and simplify: x2 – x –

✔ 20

= x2 – 3x.

Solve for x: x =

✔ 10

.Step-by-step explanation: